The impact of the EU takeover directive on takeover performance and empire building - Humphery-Jenner, Mark (Journal of Corporate Finance, 2012)
This paper uses the EU takeover directive as a natural experiment to test when legal harmonization creates value, and to examine the impact of increased entrenchment on investment decisions. The EU promulgated the takeover directive in April 2004. The implementation deadline was May 2006. The goal was to encourage value-creating takeovers by harmonizing takeover laws across the EU. However, the takeover directive has received criticism for being vague and discretionary, and for entrenching managers. I hypothesize that because the directive hinders takeovers, it might increase managerial entrenchment and enable managers of EU-companies to make agency-motivated investments (or simply exercise less discipline). I find supportive evidence: after the directive, EU-companies make investments that are less profitable (as proxied by takeover returns) and that take longer to compete. Further, asset growth increased in treated companies following the takeover directive, suggesting that the additional entrenchment facilitates empire building.